Research on Health Condition Monitoring for Glass Panel of Hidden Frame Glass Curtain Wall Under Wind Load Using Fuzzy Comprehensive Evaluation - Letian Ding; Wei Cao; Zhiyang Cao; Yifan Wang; Rui Su; Ziqi Chen; Muhammad Maqsood; Niraj Khara; Mu Liming (Shock and Vibration)
Under the excitation of strong wind load, the hidden frame glass curtain wall leads to the attenuation of safety performance, the fragmentation of glass panel, and the shedding of glass panel, which has a serious impact on the economic and social development and people’s safety. In this paper, a new health monitoring method was proposed for the glass panel of hidden frame glass curtain wall. The fuzzy comprehensive evaluation theory was used to establish the comprehensive evaluation model of the hidden frame glass panel. The factor set of the comprehensive evaluation model was established by the air tightness, deflection, natural frequency, and vibration amplitude of the hidden frame glass panel. The safety performance was divided into four levels of evaluation set, and the weight of each factor was calculated by analytic hierarchy process. The vibration signals of glass panel under different wind load conditions were processed by using the method of Hilbert vibration decomposition and envelope spectrum analysis, and the peak value and area of envelope spectrum were extracted to judge the vibration amplitude of glass panel, which was used as the evaluation index. The fuzzy comprehensive evaluation matrix was calculated by using the appropriate fuzzy operator, and the safety level of the glass panel was judged by using the principle of maximum membership degree for the calculation results. The feasibility of the method is proved by experiments, and it provides a theoretical basis for the subsequent health status monitoring of hidden frame glass curtain wall.